Effects of L-dopa during auditory instrumental learning in humans. - Tina Weis (Public Library of Science (PLoS), 2012)
The dopaminergic neurotransmitter system is critically involved in promoting plasticity in auditory cortex. We combined functional magnetic resonance imaging (fMRI) and a pharmacological manipulation to investigate dopaminergic modulation of neural activity in auditory cortex during instrumental learning. Volunteers either received 100 mg L-dopa (Madopar) or placebo in an appetitive, differential instrumental conditioning paradigm, which involved learning that a specific category of frequency modulated tones predicts a monetary reward when fast responses were made in a subsequent reaction time task. The other category of frequency modulated tones was not related to a reward. Our behavioral data provides evidence that dopaminergic stimulation differentially impacts on the speed of instrumental responding in rewarded and unrewarded trials. L-dopa increased neural BOLD activity in left auditory cortex to tones in rewarded and unrewarded trials. This increase was related to plasma L-dopa levels and learning rate. Our data thus provides evidence for dopaminergic modulation of neural activity in auditory cortex, which occurs for both auditory stimuli related to a later reward and those not related to a reward.